Evaluation of the management of a first crisis of atrial fibrillation in a group of Cameroon’s urban setting subjects - Tasong, Loïc Alban Mbosso; Nganou-Gnindjio, CN; Yemele, Honoré Kemnang; Elong, Jules Thierry; Kuate, Laura Murielle Makowa; Kuissu, Simeon; Menanga, Alain Patrick (BMC cardiovascular disorders, 2024)
Background Atrial fibrillation (AF) is the most common arrhythmia encountered in clinical practice. When atrial fibrillation is first diagnosed, it tends to be permanent and associated with significant morbidity and mortality. We aimed to study the management of a first episode of atrial fibrillation in a group of patients in Yaounde, Cameroon. Methods We conducted a retrospective study with data collected from the Cardiology department of Yaounde Central Hospital and the internal medicine department of Yaounde General Hospital over five years (January 2017 to December 2021), for a duration of 4 months, from February 2022 to May 2022. All patients older than 15 years with a first episode of atrial fibrillation were included, and all patients with incomplete medical records were excluded. The association between different variables was assessed using a χ² test and logistic regression method with a significance threshold of p < 0.05. Results Of the 141 patients recruited, the mean age was 68.5 ± 10.6 years. The sex ratio (M/F) was 0.7. The main associated factors and co-morbidities were hypertension in 70.2% (99) patients, heart failure in 36.9% (52) patients and a sedentary lifestyle in 33.3% (47) patients. The most common anticoagulant treatment was AntiVitamin K, used in 64.5% (91) of patients. Heart rate control was the most commonly used symptom control strategy in 85.1% (120) patients, mainly with beta-blockers in 52.5% (74). We found 1.4% (2) participants who were not treated with antithrombotics as recommended. Treatment of arrhythmia due to co-morbidities was not always recommended. The complication rate was 94.3% (133) patients. Control of the bleeding risk due to antithrombotic therapy and monitoring of anticoagulant therapy were not optimal. The heart rate control strategy had a higher success rate, and the sinus rhythm maintenance rate at one year was 61.7% (37) participants. Conclusion The management of a first episode of atrial fibrillation at Yaoundé’s Central and General Hospitals is not always performed according to current recommendations and is far from optimal. However, nearly two out of three patients maintained sinus rhythm for one year.